Política e imaginários no enfrentamento da LGBTIfobia : a abordagem do Canal das Bee sobre o "kit-gay" e a "ideologia de gênero" nas eleições presidenciais de 2018 - Philippe Oliveira Abouid (2020)
This research is interested in a phenomenon that is peculiar to this society immersed in digital environments - which marks the first two decades in the 21st century - and which deals with the ways of facing LGBTIphobia from an audiovisual language and shared with thousands of people. Here we are going to talk specifically about the videos published on "Canal das Bee", which is hosted on YouTube and has over 372,000 subscribers and 33 million views. This channel, as presented in the description, was created to combat homophobia, lesbophobia, biphobia, transphobia, and machism. As a temporal and thematic cut, we will focus on the 2018 presidential election scene, clearly marked by LGBTIphobia, which has strongly crossed candidates' government programs, electoral campaigns, and controversies over "Kit-Gay" and "Gender Ideology". We will observe how the facing of LGBTIphobia affects the channel to investigate how this phenomenon is capable of mobilizing the “Canal das Bee” during the brazilian election period. For the analysis of textualities, we will work with the perspective of Castoriadis (2000) in his effort to recover the productive power of the socio-historical imaginary, which we put here in dialogue with the perspectives on the politics of Arendt (2018), the politics of enmity of Mbembe (2017) and the discussion of bodies that are not bereaved developed by Butler (2018).